Differentiation of functional gastrointestinal disorders from healthy volunteers by lactulose hydrogen breath test and test meal. Issue 5 (18th December 2018) - Schindler, Valeria; Giezendanner, Stéphanie; Bütikofer, Simon; Murray, Fritz; Runggaldier, Daniel; Schnurre, Larissa; Zweig, Annina; Fried, Michael; Pohl, Daniel
Abstract: Background and Aim: Functional dyspepsia (FD) is a common disorder of gut–brain interaction with incompletely understood pathophysiology. Consequently, heterogeneous expert opinions on diagnostic tests and assessment of treatment efficacies exist. So far, no consensus about the most relevant diagnostic and outcome tool has been reached. In this study, we aimed to analyze the significance of a combined lactulose hydrogen breath test (LHBT) and liquid meal, yet representing a standardized test in irritable bowel syndrome (IBS), in FD. Methods: We analyzed data of 146 FD, 204 IBS patients, and 50 healthy volunteers (HV). All patients underwent LHBT with a meal‐drink consisting of 30‐g Lactulose and 400‐mL Ensure®. Effect of abdominal symptom generation in FD/IBS compared with HV was assessed on a patient‐reported Likert‐scale. Results: There was a significant difference between FD/IBS patients and HV in LHBT‐induced abdominal pain (odds ratio [OR] 246.9, 95% confidence interval [CI] 26.6–2290.7; OR 161.2, 95% CI 16.9–1534.8), abdominal bloating (OR 384.8, 95% CI 92.9–2135.4; OR 524.1, 95% CI 114.7–3432.3), borborygmi (OR 9.9, 95% CI 2.2–46.9; OR 17.7, 95% CI 4.7–67.4), nausea only in FD (OR 174.4, 95% CI 15.5–5375.5), and diarrhea in IBS only (OR 25.8, 95% CI 2.0–7012.6). Hydrogen production was not significantly different in FD/IBS and HV. Conclusions: In this study, we demonstrated significant differences in postprandial symptom generation in FD and IBS compared with HV after LHBT. This does not only allow us to discriminate FD/IBS from HV but may also represent a diagnostic and monitoring tool for FD/IBS in the future, including monitoring of treatment effects.